O peso que não é medido pela balança : as repercussões da obesidade no cotidiano dos sujeitos - Scherer, Patrícia Teresinha (2012)
According to the Ministry of Health (2010) obesity is considered a global epidemic and in the case of Brazil, pictures of obesity, are becoming far more frequent than the low weight in childhood. This shows that the country is experiencing an epidemiological transition process that cannot be neglected by the public health. Obesity is also considered as a risk factor for many other diseases as diabetes, stroke, heart attack, hypertension, cancer, among many others. Thus, obesity affects a variety of ways in the everyday lives of people. This survey, conducted in the Brazilian Post and Telegraph Company (ECT) Board of Rio Grande do Sul, in Porto Alegre RS, which aims to investigate the effects of obesity in the daily life of the obese subjects interviewed (11 obese adults, through a form with open questions and semi-structured script. The proposal was submitted to the Commission Investigative Science Faculty of Social PUCRS and the Ethics Committee in Research of the University. The benchmark dialectical-critical directed all research and the construction of the systematization of the results obtained. The categories of the method used for the analysis and interpretation of data were: historicity, contradictions and all. The explanatory categories of reality elected were: obesity, daily life, public policies and work. During the process of interpretation of the results led to the following empirical categories: disorders in the physical and mental health, social isolation, pain, accessibility, bariatric surgery, clothing, aesthetics and prejudice. The survey results show how obesity impacts in various ways, in everyday subjects and how many difficulties and prejudices must be overcome every day. The almost total ignorance of the subject with respect to public policies to address the prevention and treatment of obesity was another result of research that deserves to be questioned. Thus, we see the need, increasingly, to worry about this issue, proposing actions and state intervention in this worldwide epidemic